Evaluasi Petugas Security Terhadap Pengamanan di Bandara Ngurah Rai Bali - Muhammad Yusuf (WARTA ARDHIA, 2010)
In the world of flight at this time that a top priority is safety security at the airport. This is of course by looking at the growth of passenger air transport, especially Ngurah Rai Airport in Bali has increased significantly, the airport is one of the international gateway entrances are strongly associated with the level of security safety of flight services.For that security needs to be improved and are strongly associated with its implementation in terms of its is a skill and availability of human resources / security, such as eg often the case in some airports is the escape of drugs, carrying obects that are protected/sharp weapon and others.By looking at the perception of air transport passengers Ngurah Rai Airport in Bali against the security guards, which look at the attitude, behaviors, skills, where the results of an opinion stating casual assessment of the performance of the security guards. This it is to improve the performance of the security guard, so that the establishment of frust against the security of passengers at airports.